Lipid Binding Requirements for Oxysterol-binding Protein Kes1 Inhibition of Autophagy and Endosome-trans-Golgi Trafficking Pathways - LeBlanc, Marissa A. (American Society for Biochemistry and Molecular Biology, 2010)
The Saccharomyces cerevisiae protein Kes1/Osh4 is a member of the enigmatic family of oxysterol-binding proteins found throughout Eukarya united by a β-barrel structure that binds sterols and oxysterols. In this study, we determined that phosphoinositides are the major determinant in membranes that facilitate Kes1 association both in vitro and in cells. Increased expression of Kes1 in yeast cells decreased the levels of both phosphatidylinositol 4-phosphate (PI4P) and phosphatidylinositol 3-phosphate (PI3P). Phosphoinositide and sterol bindings by Kes1 were necessary for Kes1 to decrease the level of PI4P but not PI3P. Kes1 inhibited vesicular trafficking between the trans-Golgi and plasma membrane as evidenced by accumulation of the vacuolar soluble NSF attachment protein receptors Snc1 in the cytoplasmic vesicles. Sterol and phosphoinositide binding by Kes1 both contributed to its regulation of Snc1 trafficking. This study also describes a previously unknown role for Kes1 in the regulation of the autophagy/cytoplasm to the vacuole trafficking pathway. The Kes1-mediated regulation of the autophagy/cytoplasm to the vacuole trafficking pathway was prevented by increasing expression of the PI3K Vps34, suggesting that it is the Kes1-mediated decrease in PI3P level that contributes to this regulation.